Kompetensi Manajemen SDM Berbasif Ekonomi Kreatif - Ratnasari, Wahyu; Halim, Abdul; Mulia, Hamdana; Saragih, Dothy Amelia (Universitas Muhammadiyah Mataram, 2024)
Abstract: The competence of MSME HR Management often receives less attention. Often, HR is only seen as a mere means of production. The purpose of this service is to provide training and assistance to MSME actors in Balikpapan city about human resource competencies such as aspects of labor law compliance, recruitment, personnel administration, wage determination, performance assessment, The method in the implementation of this service activity is the distribution of materials, lectures, questions and answers and discussions. The results of the service activities show that this training has a significant positive impact on the ability and readiness of MSME actors in facing economic challenges and taking advantage of existing opportunities.Abstrak Kompetensi Manajemen SDM UMKM seringkali kurang mendapat perhatian. Seringkali, SDM hanya dipandang sebagai alat produksi semata. Tujuan pengabdian ini adalah untuk memberikan pelatihan dan pendampingan kepada para pelaku UMKM kota Balikpapan tentang kompetensi SDM seperti aspek kepatuhan hukum ketenagakerjaan, rekrutmen, administrasi kepegawaian, penetapan upah, penilaian kinerja, Metode dalam pelaksanaan kegiatan pengabdian ini adalah pembagian materi, ceramah, tanya jawab dan diskusi. Hasil kegiatan pengabdian menunjukkan bahwa pelatihan ini memberikan dampak positif yang signifikan terhadap kemampuan dan kesiapan pelaku UMKM dalam menghadapi tantangan ekonomi dan memanfaatkan peluang yang ada